Pengukuran Layanan Sistem Informasi Akademik menggunakan Service Intelligence dan Control the Processing of Information - Adelia Adelia; Diana Trivena Yulianti; Tiur Gantini; Remaydo Timothy Gultom (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
The development and use of information technology today cannot be avoided by most organizations, including one of the universities in Bandung. Universities have utilized information technology to support processes and activities that occur within universities, especially academic processes. Processes related to academics are supported by a new academic information system that has just been implemented, to complement the previous academic information system. In addition to the use of information technology at the university, information technology services are also an important part so that information technology can be provided according to user needs and affect user satisfaction. Analysis of the management of academic information system services needs to be done to find out services related to academic information systems and information systems according to user needs and can provide satisfaction to users, especially in the academic field. The analysis was carried out using the criteria on service intelligence and COBIT 5.0 DSS06.02 control the processing of information.